2020
DOI: 10.3389/fpsyg.2020.00461
|View full text |Cite
|
Sign up to set email alerts
|

Internalizing Symptoms in Developmental Dyslexia: A Comparison Between Primary and Secondary School

Abstract: Although the relationship between developmental dyslexia (DD) and the risk of occurrence of internalizing symptomatology has been widely investigated in the extant literature, different findings have been reported. In this study, two experiments with two general purposes are presented. The first study investigates whether the differences in the severity of internalizing symptoms between DD and controls are greater in students attending secondary school than in those attending primary school. Sixtyfive DD and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 61 publications
3
38
2
1
Order By: Relevance
“…This in turn might result in difficulties in interpersonal relationships and the development of psychological comorbidities, as well as problems in patient–physician interactions and decreased medication adherence ( Agostini et al, 2019 ; Colonnello and Agostini, 2020 ). This hypothesis is further supported by neuroimaging studies of patients with IBD, which found alterations in brain areas (e.g., the midcingulate cortex), that are involved in emotion processing ( Agostini et al, 2011 , 2013a , b , 2017 ; Vogt, 2013 ; Zikou et al, 2014 ; Kragel et al, 2018 ; Hou et al, 2019 ; Colonnello and Agostini, 2020 ; Fan et al, 2020 ; Skrobisz et al, 2020 ; Thomann et al, 2020 ; Turkiewicz et al, 2021 ; Yeung, 2021 ). This is in line with previous studies that reported that IBD patients are characterized by mentalizing deficits compared to healthy controls (HCs).…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…This in turn might result in difficulties in interpersonal relationships and the development of psychological comorbidities, as well as problems in patient–physician interactions and decreased medication adherence ( Agostini et al, 2019 ; Colonnello and Agostini, 2020 ). This hypothesis is further supported by neuroimaging studies of patients with IBD, which found alterations in brain areas (e.g., the midcingulate cortex), that are involved in emotion processing ( Agostini et al, 2011 , 2013a , b , 2017 ; Vogt, 2013 ; Zikou et al, 2014 ; Kragel et al, 2018 ; Hou et al, 2019 ; Colonnello and Agostini, 2020 ; Fan et al, 2020 ; Skrobisz et al, 2020 ; Thomann et al, 2020 ; Turkiewicz et al, 2021 ; Yeung, 2021 ). This is in line with previous studies that reported that IBD patients are characterized by mentalizing deficits compared to healthy controls (HCs).…”
Section: Introductionmentioning
confidence: 72%
“…With regard to the psychological burden of anxiety and depression, the direction of (neuro-)inflammatory processes and disease activity in CD/UC seems to be bidirectional – with patients with anxiety symptoms developing more often disease flares, and patients with disease activity developing more anxiety ( Gracie et al, 2018 ). Additionally, recent neuroimaging studies have shown that patients with (active) IBD have an altered brain structure, which is associated with symptoms of depression and anxiety ( Agostini et al, 2011 , 2013a , b , 2017 ; Vogt, 2013 ; Zikou et al, 2014 ; Kragel et al, 2018 ; Hou et al, 2019 ; Colonnello and Agostini, 2020 ; Fan et al, 2020 ; Skrobisz et al, 2020 ; Thomann et al, 2020 ; Turkiewicz et al, 2021 ; Yeung, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, our survey suggested that the school closure may impact also the social condition of children with learning difficulties: this could be in part a consequence of the internalizing comorbidities frequently seen in these children [ 21 ] but could also reflect an increased burden of distress caused by the feeling of an increased inadequacy coupled with a larger amount of time requested to fulfill school duties [ 3 ].…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Finally, the present study has focused on a narrow academic aspect of reading difficulties. Future research is warranted to focus on the holistic identification of reading difficulties and the evaluation of the ecological, emotional, psychosocial, behavioral aspects, and strategies that are predictive of the overall success of individuals with reading disabilities and learning disabilities ( Giovagnoli et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the cycles of academic struggles lead to further academic failure, psychosocial, and behavior problems as disapproval of parents, teachers, and peers regarding the school performance have an impact on the children's feelings of inferiority and helplessness (Greenham, 1999). These risk factors of psychosocial and behavioral problems among children with reading problems are developmentally cumulative across grades starting early at preschool and primary school (Halonen et al, 2006;Giovagnoli et al, 2020). The complex contextual interaction between various individual, psychosocial, and environmental factors derive a host of internalizing and externalizing mental health problems such as depressive symptoms and disorders (Livingston et al, 2018).…”
Section: Introductionmentioning
confidence: 99%